Pattern of left main stenosis at a tertiary cardiac center of Nepal - Rauniyar, Binay Kumar; Gautam, Milan; Sharma, Ranjit; Kansakar, Subodh Bir Singh; Rajbhandari, Rajib; Maskey, Arun; Malla, Rabi (Nepalese Heart Journal, 2017)
Background and Aims: Left main stem stenosis is defined as a lesion occupying more than 50% of the lumen diameter. Various studies have shown that left main stem stenosis occurs in 4%-6% of all the patients undergoing coronary angiography. We aim to find out the pattern of Left main stem disease in cardiology department of a tertiary cardiac center of Nepal. Methods: This was a retrospective study and was conducted from the properly maintained record of 2 years (August 2011 to July 2013) from cardiaccatheterization labs of Shahid Gangalal National Heart Centre, Bansbari, Kathmandu, Nepal. Results: During the study period 3290 coronary angiogram were done. Among them 102 (3.1%) patients had left main stem stenosis of more than 50%. Mean age of the patients with left main stem stenosis was 60.6±10.1yrs. Most of (73.5%) of patients with left main stem stenosis were of age more than 55 years. Most (80.3%) of them were male. Ostial left main stem stenosis was present in 32 (31.3%) patients whereas distal left main stem stenosis was present in 70 (68.6%) patients. In patients with Left main stem stenosis, single vessel disease was present in 12 (11.7%), double vessel disease in 33(32.3%) and triple vessel disease in 49 (48.0%) patients, whereas 8 (7.8%) patients with non-critical coronary artery disease. Conclusion: Left main stem disease is not an uncommon angiographic finding and is often associated with multivessel coronary artery disease. It commonly occurs in distal part of vessel and the patients were older males. Nepalese Heart Journal 2017; 14(1): 29-30